2022
DOI: 10.1002/aic.17834
|View full text |Cite
|
Sign up to set email alerts
|

Porous washcoat structure in CeO2 modified Cu‐SSZ‐13 monolith catalyst for NH3‐SCR with improved catalytic performance

Abstract: A series of CeO2 modified Cu‐SSZ‐13 monolith catalysts were prepared by embedding CeO2 into the washcoat of Cu‐SSZ‐13 monolith catalyst through solvent combustion method. These CexCu‐SSZ‐13 catalysts were studied in the selective catalytic reduction (SCR) of NO with NH3, among which the Ce2Cu‐SSZ‐13 catalyst exhibited the best low‐temperature activity, hydrothermal stability, and sulfur resistance. The physicochemical properties of the catalysts were characterized using multiple methods. Results showed that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 50 publications
(107 reference statements)
0
1
0
Order By: Relevance
“…The monolithic catalysts have always been required for practical application because of their advantages of a low pressure drop as well as good mass and heat transfer properties in actual industrial reaction units. , Hereby, we coated the preferred SN 0.10 M 0.90 catalyst on a cordierite honeycomb carrier using a wash-coating process to prepare the SN 0.10 M 0.90 /cordierite monolithic catalyst and evaluated its propane catalytic oxidation performance. As displayed in Figure d, it can be found that when the reaction temperature was <450 °C, the higher the H 2 O content of the feed gases is, the higher is the inhibition effect on the catalytic performance.…”
Section: Resultsmentioning
confidence: 99%
“…The monolithic catalysts have always been required for practical application because of their advantages of a low pressure drop as well as good mass and heat transfer properties in actual industrial reaction units. , Hereby, we coated the preferred SN 0.10 M 0.90 catalyst on a cordierite honeycomb carrier using a wash-coating process to prepare the SN 0.10 M 0.90 /cordierite monolithic catalyst and evaluated its propane catalytic oxidation performance. As displayed in Figure d, it can be found that when the reaction temperature was <450 °C, the higher the H 2 O content of the feed gases is, the higher is the inhibition effect on the catalytic performance.…”
Section: Resultsmentioning
confidence: 99%